Abbreviations and Acronyms: The Case of Tlhalosi ya Medi ya Setswana - Mathangwane, Joyce T. (Lexikos, 2015)
This paper looks at how abbreviations and acronyms are treated in African language dictionaries in general compared to selected mainstream English dictionaries. Specifically, the study looks at their treatment in T.J. Otlogetswe’s (2012) Tlhalosi ya Medi ya Setswana dictionary. Altogether, a survey of twenty selected dictionaries was carried out examining the treatment of abbreviations and acronyms in these dictionaries. Ten of these dictionaries are mainstream English dictionaries and the remaining ten are dictionaries of varied African languages spoken in the Southern African region e.g. Shona, Ndebele, Venda, Setswana and Northern Sotho. The study addresses four questions: (a) whether African lexicographers include abbreviations and acronyms in their dictionaries as is practice in mainstream English dictionaries; (b) if so, how these have been treated; (c) what linguistic features are highlighted in these entries, if any; and, (d) what recommendation the study makes for the way forward. The results showed that in most of the African dictionaries in the survey, unlike in mainstream English dictionaries, abbreviations and acronyms are not included despite the fact that many of them are coined and used by native speakers of these languages. An exception is Otlogetswe (2012) with a list of 25 abbreviations and acronyms. The paper recommends that African lexicographers include abbreviations and acronyms as part of their lexicon because these lexical items are coined by the communities making them part of the vocabulary of the language. Users of these dictionaries should find entries of abbreviations and acronyms in these dictionaries whenever they want to confirm the meaning, or when teaching.